Advanced paddy field engineering (Shizan-sha, 1999)
Development of paddy field engineering in Japan, paddy soils, irrigation water requirement, irrigation system design, automatic operation of irrigation systems, runoff analysis of paddy field based watershed, farm machinery for rice cultivation.